Slow on the Uptake, Progression to Heartbreak - Ashley K. Binder MD; John P. Haydek MD; Siddhant Parihar MD; Chelsea E. Modlin MD; Manasi Tannu MD; Amalia Aldredge MD; Viranuj Sueblinvong MD (SAGE Publishing, 2020)
The prevalence of serotonin syndrome increases over the past several years as more serotonergic medications are being used in clinical practice. It is a potentially lethal condition caused by excessive serotonergic activity. Common causes of serotonin syndrome are the use of prescription medications, illicit drugs, or a combination of substances, leading to an increase in the activity of serotonin in the central and peripheral nervous system. The clinical symptoms range from mild to severe. We report a case of a 25-year-old woman with polysubstance abuse, including cocaine, who presented with confusion, rigidity, high-grade fever, and reduced biventricular function on echocardiogram. Based on the combination of substance used history, clinical presentation, and echocardiogram findings, she was diagnosed with serotonin syndrome complicated by takotsubo cardiomyopathy. She improved after being treated in the intensive care unit and was discharged from the hospital. This patient demonstrates the importance of recognizing and promptly initiating management of serotonin syndrome in order to improve morbidity and mortality.